FAKTOR-FAKTOR YANG MEMPENGARUHI PERUBAHAN KEBIJAKAN TERHADAP STATUS KAWASAN STRATEGIS TANJUNG BERIKAT PADA PERUBAHAN RTRW KABUPATEN BANGKA TENGAH - Fradita Sandi; Yori Herwangi (LPPM STIE PERTIBA Pangkalpinang, 2020)
A common problem often faced by local government, is the underdevelopment and inequality. To overcome this problem and to be able to compete with other regions, Central Bangka Regency seeks to accelerate economic development through the development of the Tanjung Berikat Strategic Zone. It has been planned since 2011 in the Regency Spatial Plan by establishing it as KSK and KSP. However, in 2019, the Central Bangka Regency Government has changed its policy by not establishing Tanjung Berikat as the KSK. This study aims to identify the factors that influence the policy changes of the Central Bangka Regency Government about status of the Tanjung Berikat Strategic Zone on the change of the Central Bangka Regency spatial plan. The method used in this study is a qualitative research method with a descriptive approach. Data collection techniques used are observation, interview and documentation. The results of this study indicate that the policy change towards the status of the Tanjung Berikat Strategic Zone at the change of Bangka Tengah Regency spatial plan is due to changes in opinion on the plan, the lessons learned from previous experience, and also part of the strategy to realize the plan.